Survival outcomes in patients with gastric and gastroesophageal junction adenocarcinomas treated with perioperative chemotherapy with or without preoperative radiotherapy. Issue 1 (18th September 2019) - Tian, Sibo; Jiang, Renjian; Madden, Nicholas A.; Ferris, Matthew J.; Buchwald, Zachary S.; Xu, Karen M.; Cardona, Kenneth; Maithel, Shishir K.; McDonald, Mark W.; Lin, Jolinta Y.; Curran, Walter J.; El‐Rayes, Bassel F.; et al.
Abstract : Background: Perioperative chemotherapy (POC) is one standard approach for the treatment of resectable cancers of the stomach and gastroesophageal junction (GEJ), whereas there has been growing interest in preoperative therapies. The objective of the current study was to compare survival between patients treated with preoperative chemoradiotherapy and adjuvant chemotherapy (PCRT) with those receiving POC using a large database. Methods: The National Cancer Data Base was queried for patients diagnosed between 2004 and 2013 with American Joint Committee on Cancer clinical group stage IB to stage IIIC (excluding T2N0 disease) adenocarcinoma of the stomach or GEJ. Patients treated with definitive surgery and POC with or without preoperative radiotherapy of 41 to 54 Gy were included. Overall survival (OS) was defined from the date of definitive surgery and estimated using the Kaplan‐Meier method. A total of 14 patient and treatment variables were used for propensity score matching (PSM). Results: A total of 1048 patients were analyzed: 53.2% received POC and 46.8% received PCRT. The primary tumor site was the GEJ in 69.1% of patients and stomach in 30.9% of patients. The median age of the patients was 60 years, and the median follow‐up was 25.8 months. The use of PCRT was associated with a greater pathologic complete response rate of 13.1% versus 8.2% ( P = .01). POC was associated with a decreased risk of death in unmatched groups (hazard ratio [HR], 0.83; P = .043). Using PSM cohorts, POC decreased the risk of death with a median OS of 45.1 months versus 31.4 months (HR, 0.70; P = .016). The 2‐year OS rate was 72.9% versus 62.5% and the 5‐year OS rate was 40.7% versus 33.1% for POC versus PCRT, respectively. Survival favored POC in PSM gastric (HR, 0.41; P = .07) and GEJ (HR, 0.77; P = .08) patient subgroups. Conclusions: The addition of preoperative radiotherapy to POC appears to be associated with an increased risk of death in patients with resectable gastric and GEJ cancers. Abstract : The addition of preoperative radiotherapy to perioperative, multiagent chemotherapy is associated with an increased risk of death in patients with resectable gastric and gastroesophageal adenocarcinoma, despite a higher pathologic complete response rate and equivalent short‐term mortality. The median overall survival in the current study is reported to be 45.1 months versus 31.4 months favoring perioperative chemotherapy alone based on propensity score matched cohorts using 14 patient, disease, and treatment variables.